2021
DOI: 10.1177/23969415211035666
|View full text |Cite
|
Sign up to set email alerts
|

Inferential narrative comprehension ability of young school-age children on the autism spectrum

Abstract: Background and aims The purpose of the current exploratory study was to describe the inferential narrative comprehension skills of young school-age children on the autism spectrum who, as a group, are at high risk of significant and persistent reading comprehension difficulties. Our aim was to investigate whether the anticipated difficulties in inferential narrative comprehension in the group of children with autism could be explained by the children’s structural language ability as measured using a broad-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
2
1
0
Order By: Relevance
“…Analysis of the distribution of narrative comprehension scores revealed that the scores were normally distributed and therefore at a suitable level of difficulty for this age group. Consistent with other studies (Westerveld et al, 2021), comprehension of factual information was easier than understanding inferred meaning for 5-year-old children. These data have practical implications for teaching practice.…”
Section: Discussionsupporting
confidence: 90%
“…Analysis of the distribution of narrative comprehension scores revealed that the scores were normally distributed and therefore at a suitable level of difficulty for this age group. Consistent with other studies (Westerveld et al, 2021), comprehension of factual information was easier than understanding inferred meaning for 5-year-old children. These data have practical implications for teaching practice.…”
Section: Discussionsupporting
confidence: 90%
“…The growth of Hcy can produce oxygen free radicals (23) and hydrogen peroxide, and can also inhibit the activities of other antioxidant enzymes and promote lipid peroxidation. Therefore, a higher Hcy level will lead to autism, and the serum Hcy level of autistic children will be higher than that of normal children, which is consistent with the results of this study (24).…”
Section: Correlation Between Hcy 5-ht Vitamin B12 Levels and Autismsupporting
confidence: 91%
“…In this study, young participants were directed to engage with a culturally adapted narrative titled "Alice and the Suitcase," crafted by Dr. Westerveld and her team (Westerveld et al, 2021). The participants, children in this instance, were asked to both listen to the narrated story and simultaneously view corresponding images displayed on a computer screen.…”
Section: Story Re-tell Taskmentioning
confidence: 99%